2016
DOI: 10.1016/j.bbamcr.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Actin related protein complex subunit 1b controls sperm release, barrier integrity and cell division during adult rat spermatogenesis

Abstract: Actin remodeling is a vital process for signaling, movement and survival in all cells. In the testes, extensive actin reorganization occurs at spermatid-Sertoli cell junctions during sperm release (spermiation) and at inter Sertoli cell junctions during restructuring of the blood testis barrier (BTB). During spermiation, tubulobulbar complexes (TBCs), rich in branched actin networks, ensure recycling of spermatid-Sertoli cell junctional molecules. Similar recycling occurs during BTB restructuring around the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Studies have demonstrated that inhibition of the CD74 signaling pathway induced testicular immunosuppression and fibrosis ( Li et al, 2022 ). ARPC1B is a regulator of spermatogenesis, the blood-testis barrier and cell division ( Kumar et al, 2016 ). APOA1 mRNA exists in sperm and plays an important role in maintaining sperm motility, survival rate and fertilization process ( Chi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that inhibition of the CD74 signaling pathway induced testicular immunosuppression and fibrosis ( Li et al, 2022 ). ARPC1B is a regulator of spermatogenesis, the blood-testis barrier and cell division ( Kumar et al, 2016 ). APOA1 mRNA exists in sperm and plays an important role in maintaining sperm motility, survival rate and fertilization process ( Chi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the protein coded by this gene is present in the APR2/3 complex, it may have a role in the organization of the actin cytoskeleton and function as an ATP-binding component of the Arp2/3 complex, which is involved in the regulation of actin polymerization. This complex is a regulatory protein in the actin cytoskeleton and induces cell-shape change and motility [ 64 , 65 ]. Actin filament-based process, actin cytoskeleton organization, actin binding, cytoskeletal protein binding and actin cytoskeleton were the highly associated GO terms affected by the ACTR3B gene.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 4 cytoskeletons (actin, micro, intermediate filament, and septum) supporting spermatogenesis are found in the testis. Regulation of actin cytoskeleton as one of them plays a crucial role in mammalian testicular spermatogenesis ( Kumar et al, 2016 ; Tang et al, 2016 ; Liu et al, 2020 ). In this study, through KEGG enrichment analysis, we found a significantly enriched pathway regulation of actin cytoskeleton, and differential genes in the regulation of actin cytoskeleton pathway were validated by qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%